Authenticization: Consuming commodified authenticity to become “authentic” subjects - Plesa, Patric (Theory & psychology, 2023)
Research on authenticity continues to grow in diverse fields and under various definitions. I argue that the concept of authenticity has become a marketable self-branding strategy to meet the ends of neoliberal capitalism with often consequential and contradictory effects on subjectivity. Using Lehman et al.’s (2019) review of the various definitions of authenticity in the literature, I claim that a process I am calling authenticization overlaps the diverse and contradictory definitions to produce commodified forms of authenticity. The production and consumption of commodified forms of authenticity reflect the neoliberal norms of individualization, responsibilization, and self-governance, which, through the process of authenticization, become values that reshape “authentic” self-expression. Self-understanding and freedom are compromised in the production and consumption of commodified forms of authenticity with potential consequences for identity and mental health.